2012
DOI: 10.2478/s13540-012-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies for the variable-order nonlinear fractional wave equation

Abstract: In this paper, the explicit finite difference method (FDM) is used to study the variable order nonlinear fractional wave equation. The fractional derivative is described in the Riesz sense. Special attention is given to study the stability analysis and the convergence of the proposed method. Numerical test examples are presented to show the efficiency of the proposed numerical scheme.MSC 2010 : 26A33, 65K10, 65G99, 35E99 Key Words and Phrases: variable order fractional calculus, nonlinear fractional wave equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…In the literature of fractional calculus, several different definitions of derivatives are found . One of those, introduced by (Caputo, 1967) and studied independently by other authors, like (Džrbašjan and Nersesjan, 1968) and (Rabotnov, 1969), has found many applications and seems to be more suitable to model physical phenomena (Dalir and Bashour, 2010;Diethelm, 2004;Machado et al, 2010;Murio and Mejía, 2008;Singh, Saxena and Kumar, 2013;Sweilam and AL-Mrawm, 2011;Yajima and Yamasaki, 2012).…”
Section: Caputo-type Fractional Operators Of Variable-ordermentioning
confidence: 99%
“…In the literature of fractional calculus, several different definitions of derivatives are found . One of those, introduced by (Caputo, 1967) and studied independently by other authors, like (Džrbašjan and Nersesjan, 1968) and (Rabotnov, 1969), has found many applications and seems to be more suitable to model physical phenomena (Dalir and Bashour, 2010;Diethelm, 2004;Machado et al, 2010;Murio and Mejía, 2008;Singh, Saxena and Kumar, 2013;Sweilam and AL-Mrawm, 2011;Yajima and Yamasaki, 2012).…”
Section: Caputo-type Fractional Operators Of Variable-ordermentioning
confidence: 99%
“…In this section, we briefly recall the main ideas of fractional calculus, when the order of integration/differentiation is allowed to vary over time. Fractional operators with variable order can be successfully used to describe several physical phenomena, as discussed in References , and among these we have the aging phenomenon, as discussed in Reference .…”
Section: Fractional Hereditary‐aging Materialsmentioning
confidence: 99%
“…In the literature of fractional calculus, several different definitions of derivatives are found [28]. One of those, introduced by Caputo in 1967 [3] and studied independently by other authors, like Džrbašjan and Nersesjan in 1968 [10] and Rabotnov in 1969 [25], has found many applications and seems to be more suitable to model physic phenomena [6,8,9,15,16,31,33,35]. Before generalizing the Caputo derivative for a variable order of differentiation, we recall two types of special functions: the Gamma and Psi functions.…”
Section: Fractional Calculus Of Variable Ordermentioning
confidence: 99%